2014
DOI: 10.5005/jp-journals-10005-1263
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Effect of Different Chemical Solvents on the Shear Bond Strength of Glass Fiber reinforced Post to Core Material

Abstract: ABSTRACT%Aim: To compare the effect of different chemical solvents on glass fiber reinforced posts and to study the effect of these solvents on the shear bond strength of glass fiber reinforced post to core material.Materials and methods: This study was conducted to evaluate the effect of three chemical solvents, i.e. silane coupling agent, 6% H2O2 and 37% phosphoric acid on the shear bond strength of glass fiber post to a composite resin restorative material. The changes in post surface characteristics after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…FRCs have been intensively investigated with a particular emphasis on mechanical properties such as fracture toughness, compressive strength, load-bearing capacity [ 4 ], flexural strength [ 5 ], fatigue resistance [ 6 ], fracture strength [ 7 ] or on the effect of layer thickness [ 8 ], bacterial adhesion [ 9 ], adhesion of fibers for various dental applications, such as long fibers [ 10 ], nets [ 11 ], and posts [ 12 ]. From clinical perspective, FRCs have been investigated for different clinical applications in prosthodontics, such as replacement of missing teeth by resin-bonded adhesive fixed dental prostheses of various kinds [ 13 ], reinforcement elements of dentures or pontics [ 14 ], and direct construction of posts and cores [ 15 ].…”
mentioning
confidence: 99%
“…FRCs have been intensively investigated with a particular emphasis on mechanical properties such as fracture toughness, compressive strength, load-bearing capacity [ 4 ], flexural strength [ 5 ], fatigue resistance [ 6 ], fracture strength [ 7 ] or on the effect of layer thickness [ 8 ], bacterial adhesion [ 9 ], adhesion of fibers for various dental applications, such as long fibers [ 10 ], nets [ 11 ], and posts [ 12 ]. From clinical perspective, FRCs have been investigated for different clinical applications in prosthodontics, such as replacement of missing teeth by resin-bonded adhesive fixed dental prostheses of various kinds [ 13 ], reinforcement elements of dentures or pontics [ 14 ], and direct construction of posts and cores [ 15 ].…”
mentioning
confidence: 99%
“…It forms a chemical bridge with hydroxyl covered substrates, such as glass. [28,39,30] Studies have reported phosphoric acid [11,[18][19][20][21]. has the ability to remove epoxy layer with intact glass fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive cementation of ceramic crowns increases the fracture resistance of the core-crown complex ( 20 ) and directly correlates with long-term clinical success. Previous studies have evaluated the adhesive relationship between post and luting agent ( 9 , 18 ), post and core material ( 21 ), luting agent and enamel/dentin ( 12 ), tooth and core materials ( 22 ), and crown and core materials ( 23 ). However, there is a lack of investigations about the bonding relationship between cement and the material used to perform the core build-up restorations.…”
Section: Introductionmentioning
confidence: 99%